Przesunięcie koncepcyjne w studiach granicznych - Jańczak, Jarosław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
Dynamic (re)development of the border studies in Europe and North America after the collapse of communism proved both (geo)political relevance of disappearing and reappearing boundaries, as well as academic interest in describing, explaining and categorizing the above-mentioned processes. They have been however homogeneous neither in empirical dimension, nor in analytical reflection. What have been observed is growing conceptual shift in border studies. It is manifested in more and more multidisciplinary approach to the field as well as new focus: social practices instead of geopolitical perspective. Consequently border studies look for their own identity and aspirate to be a separate academic discipline.
Conceptual Shift in Border Studies
Keywords: studia graniczne; border studies; zarządzanie transgraniczne; cross-border governance